2018
DOI: 10.3389/fnsys.2018.00012
|View full text |Cite
|
Sign up to set email alerts
|

Interfacing Graphene-Based Materials With Neural Cells

Abstract: The scientific community has witnessed an exponential increase in the applications of graphene and graphene-based materials in a wide range of fields, from engineering to electronics to biotechnologies and biomedical applications. For what concerns neuroscience, the interest raised by these materials is two-fold. On one side, nanosheets made of graphene or graphene derivatives (graphene oxide, or its reduced form) can be used as carriers for drug delivery. Here, an important aspect is to evaluate their toxicit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(121 citation statements)
references
References 243 publications
(343 reference statements)
3
114
0
Order By: Relevance
“…From the live-dead cell assay results, it appeared that N27 cells successfully grew on the graphene and Kapton substrate, confirming our earlier hypothesis [69,70]. It has been discussed in tissue-engineering literature that graphene may negatively affect the bimolecular mechanisms responsible for biological safety and toxicity [71][72][73][74]. Many reports have claimed that oxidative stress is one mechanism of cytotoxicity originating from carbon-based nanomaterials [75].…”
Section: Biocompatibility Testing With N27 Cellssupporting
confidence: 82%
“…From the live-dead cell assay results, it appeared that N27 cells successfully grew on the graphene and Kapton substrate, confirming our earlier hypothesis [69,70]. It has been discussed in tissue-engineering literature that graphene may negatively affect the bimolecular mechanisms responsible for biological safety and toxicity [71][72][73][74]. Many reports have claimed that oxidative stress is one mechanism of cytotoxicity originating from carbon-based nanomaterials [75].…”
Section: Biocompatibility Testing With N27 Cellssupporting
confidence: 82%
“…In our study, we have previously shown that CVD‐grown graphene combines both positive and stretched surface which are indeed two crucial features sustaining neural outgrowth, and that poor crystalline quality could significantly impede the neural adhesion and growth. Graphene also offers a flexibility at the cell scale compared to rigid substrate which could also play a significant role in the neurite sprouting and cell motility, in addition to other biosuitable properties of graphene, such as nanoscale structure, robust, mechanically deformable, electrical conductivity, and absorption of biomolecules . This unique combination gathered in a single material can indeed collectively support the neurons regrowth and improve the acceptance of the foreign interface.…”
Section: Discussionmentioning
confidence: 99%
“…In the last case, an interesting increased neurite sprouting and outgrowth induced by graphene were reported for hippocampal neurons 1 , differentiated SH-SY5Y neuroblastoma cell line 5 , adrenal phaeochromocytoma (PC12) cell line 4,6,7 , dorsal root ganglion (DRG) neurons 4 and neural stem cells 8 . Such feature makes graphene appealing for application in peripheral nerve regeneration, where an appropriate scaffold may accelerate neurite outgrowth 9,10 . However, to date, few studies have examined the interaction of graphene with peripheral neurons.…”
Section: Introductionmentioning
confidence: 99%